Flow Injection Technique for Biochemical Analysis with Chemiluminescence Detection in Acidic Media - Yanjun Fang; Jing Chen (Sensors, 2007)
A review with 90 references is presented to show the development of acidic chemiluminescence methods for biochemical analysis by use of flow injection technique in the last 10 years. A brief discussion of both the chemiluminescence and flow injection technique is given. The proposed methods for biochemical analysis are described and compared according to the used chemiluminescence system.